Cinematografando geograficamente o espaço da cidade de Extremoz na plataforma do YouTube - Lima, Raimundo Guilherme de (2020)
Based on the democratization of video production and distribution, resulting from the use of cell phones and social networks, the work aims to promote a direction that allows students to embrace the chosen pedagogical practice, which in this specific case, is the audiovisual. The effectiveness of the proposal establishes the production of videos and the addition of all its stages, such as the elaboration of the script, production, editing and publication carried out by the students with the mediation of the teacher, in order to be published on video Streaming platforms , such as YouTube on its own channel, created specifically to conduct the study. The measure attributes to students the uniqueness of protagonists in this teaching and learning process. The proposal used will be applied in the public sphere, at the Municipal School Nossa Senhora de Fátima, being developed in the curricular component of Geography, in Elementary School II, with the class of the 9th grade in the afternoon. The locus of work is the municipality of Extremoz - RN, inserted in the metropolitan region of the capital, more precisely in the rural community of Vila de Fátima. The aim of the study is to promote, through media production, the interaction between geographical concepts, worked in the educational environment with the local identity of the place. To verify the researched elements, the study tabulated the following aspects analyzed: the types of languages used by Youtubers, the Iconography of the videos, the sound, duration of the materials produced and the target audience. The verification elements mentioned were part of the set of items that worked in the process of observing the selected channels and evaluated during the research. The entire analytical procedure was based on the qualitative method. The theoretical framework was guided by a conceptual construction, attributing as parameters the following aspects: the educational system in some developed nations, the audiovisual as an educational tool and the video as a facilitating instrument for school activities. Thus, audiovisuals were conceived in their fullness and led by students. Therefore, the work reaffirms the purpose of contributing to the process, of dynamizing the educational scenario, bringing a contemporary, innovative and functional proposal regarding the improvement of students' learning.